PERAN PEREMPUAN DALAM MENUNJANG PEREKONOMIAN KELUARGA DI DESA BLUTO - Intan Komariyah; Very Andrianingsih (Journal MISSY (Management and Business Strategy), 2020)
The husband's insufficient income, in fulfilling the needs of the family, makes women who are housewives in Bluto Village choose to play dual roles as housewives and as workers in helping support the family economy. This study aims to determine the factors underlying women in supporting the family economy and how women support the family economy. This type of research is a qualitative descriptive study. The sampling technique in this study used purposive sampling by determining key informants as many as 1 person, as many as 20 main informants, 2 supporting informants and using data collection techniques, including observation, interviews, documentation. The results showed that the pressure of economic needs, the husband's income was not sufficient to meet the needs of the family so that some housewives in Bluto Village chose to do double persn in supporting the family economy. The way they do to help support the family economy is by working as farm laborers and other laborers.